Competencies of Property Valuers in Thailand - Suvarnadhada, Pabhagorn (Journal of Architectural/Planning Research and Studies (JARS), 2022)
The objectives of this research were to determine the component of the competencies of propertyvaluers in Thailand and to test the validity of the structure equation model of the competencies of propertyvaluers in Thailand with the empirical data. The sample consisted of 200 senior professional valuers. The instrumentemployed in this research was the questionnaires concerning the competencies. The data were analyzedby Confirmatory Factor Analysis. The test of the structural validity test of the competency model indicated thatthe secondary order confirmatory factor analysis of the competency of property valuers in Thailand model wereconsistent with empirical data significantly. The competency of property valuers in Thailand model were thetwo components of the competency of the property valuers in Thailand consisted of 1) core competency and2) functional competency. The five components of the core competency of the property valuers consisted ofสมรรถนะของนักประเมินมูลค่าทรัพย์สินในประเทศไทยCompetencies of Property Valuers in Thailandปภากร สุวรรณธาดาPabhagorn Suvarnadhadaบัณฑิตวิทยาลัย มหาวิทยาลัยคริสเตียน จังหวัดนครปฐม 73000Graduate School, Christian University of Thailand, Nakhonpathom, 73000, ThailandE-mail: pabhagorn@gmail.com104 JARS 10(2). 20131) Achievement Orientation, 2) Self Management, 3) Property Valuation Ethics, 4) Creative Problem Solving and5) Service and Organizational Awareness. The four components of the functional competency of the propertyvaluers consisted of 1) Property Valuation Supporting Knowledge, 2) Professional Proficiency, 3) ValuationActivity Management and 4) Real Estate Market Perception. The competencies of the property valuers inThailand could be used to develop property valuation industrial and profession, used to increase performanceof the property valuers in organizational and used to be the model to develop the property valuers who wantto certify senior professional valuer in the future.